1990
DOI: 10.7547/87507315-80-8-419
|View full text |Cite
|
Sign up to set email alerts
|

Aerobic dance survey. A study of high-impact versus low-impact injuries

Abstract: A survey of 275 aerobic dance instructors and participants was performed to determine the overall injury rate for each group, as well as the rate of injury in high-impact versus low-impact aerobics. Injuries occurred in 35% of the combined group. Instructors reported a 53% injury rate. Those who took high-impact classes had a 35% injury rate versus 24% in low-impact classes. The rate of injury was analyzed in terms of age, number of workouts, shoe type, and floor type.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
5
0
7

Year Published

1996
1996
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 0 publications
2
5
0
7
Order By: Relevance
“…Also, the present study supported that the height of the platform which was significantly positively correlated with the music bit/min level during the step exercise program was another significant predicted factor to many days of absence due to injury from the class. These results are in an accordance with many researchers [5,20,21] supported that when an aerobic instructor worked in high and mixed intensity step classes they showed a significant higher injury rate in comparison with those who worked in low impact step classes.…”
Section: Discussionsupporting
confidence: 92%
“…Also, the present study supported that the height of the platform which was significantly positively correlated with the music bit/min level during the step exercise program was another significant predicted factor to many days of absence due to injury from the class. These results are in an accordance with many researchers [5,20,21] supported that when an aerobic instructor worked in high and mixed intensity step classes they showed a significant higher injury rate in comparison with those who worked in low impact step classes.…”
Section: Discussionsupporting
confidence: 92%
“…According to the results of this study, the instructors involved in mixed or high intensity classes presented a higher injury rate in comparison to those who conducted low or moderate intensity classes, © 2013 University of Alicante which are in agreement with Janis (1990), and Harnischfeger, Raymond and Hagerman (1988). An innovation of the present study is the examining the musculoskeletal injuries in relation to different aerobic styles.…”
Section: Discussionsupporting
confidence: 78%
“…9 It should be noted that 76% of the respondents in the present study were also involved in other sporting activities, such as weight training, swimming, and running, which are likely to place stress on joints, ligaments, and muscles. The lowimpact classes were taught more frequently; the high-impact classes registered the lowest number of classes taught per week.…”
Section: Discussionmentioning
confidence: 78%
“…The study had a response rate of 37%, and the injury rate reported was 77%, which is comparable to rates in studies conducted since 1985. 7,9 Some injuries, such as knee pain, torn ligaments or hamstrings, sprains, shin splints, and stress fractures, were sustained in previous sporting activities and may have been aggravated by teaching a large number of aerobic classes, which was defined as more than three classes per day. This injury rate may be indicative of the repetitive nature of the activity performed and the constant impact of forces experienced by the lower extremity during class.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation